Differences in Mathematics Learning Outcomes in Terms of Level of Motivation and Learning Styles of Students Class XI SMK Kesehatah Imelda Ritonga - Dede Irawan; Amin Harahap (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine differences in mathematics learning outcomes of students in terms of level of motivation learning styles of students and How students ' mathematics learning Outcomes in terms of level of motivation and learning styles of students. This research experiments. The research Data consists of the initial test and final test about the material that has been delivered using the approach of learning motivation and learning styles with the dependent variable is learning outcomes. In this study, the researchers obtained data from the results of pre-test and post-test conducted in the experimental class(the class that viewed from learning motivation) and class control(class in terms of learning styles). Based on the above analysis, it has been proven that there are significant differences between the learning outcomes in terms of learning motivation and learning styles in enhancing student learning outcomes in Mathematics learning in the SMK Kesehatan Imelda Ritonga.